Developing a nomogram for predicting surgical intervention in pediatric intussusception after hydrostatic reduction - Zhuang, Yize; Wang, Xun; Fan, Xia; Li, Fei; He, Guoqing; Luo, Miao; Tang, Yingming (Frontiers in Pediatrics, 2023)
Purpose: The aim of this study was to develop and validate a nomogram for predicting surgical intervention in pediatric intussusception after hydrostatic reduction. Methods: Children with intussusception who had treated with sonographically guided saline hydrostatic reduction as an initial treatment were enrolled in this study. The enrolled patients were randomly selected for training and validation sets, and the split ratio was 7:3. The medical records of enrolled patients were retrospectively reviewed. The patients were divided into a surgery and a non-surgery group according to the results of the nonsurgical reduction. A model for predicting the risk of surgical treatment was virtualized by the nomogram using logistic regression analysis. Results: The training set consisted of 139 patients and the validation set included 74. After logistic regression analysis using training set, duration of symptoms, bloody stools, white blood cells (WBCs), creatine kinase isoenzyme (CK-MB), long-axis diameter, poor prognostic signs by ultrasound and mental state were identified as the independent predictors of surgical intervention for intussusception. A model that incorporated the above independent predictors was developed and presented as a nomogram. The C-index of the nomogram in the validation set was 0.948 (95% CI, 0.888-1.000). The calibration curve demonstrated a good agreement between prediction and observation. The decision curve analysis (DCA) curve showed that the model achieved a net benefit across all threshold probabilities. Conclusion: Based on the predictors of duration of symptoms, bloody stools, WBCs, CK-MB, long-axis diameter, poor prognostic signs by ultrasound and mental state, we developed a nomogram for predicting surgical intervention after hydrostatic reduction. This nomogram could be applied directly to facilitate pre-surgery decision for pediatric intussusception.